Phrasal Verbs and Academic Formality: Navigating The Syntax-Semantics Interface in Student Writing - Najwa Tolinggi (International Journal Labs, 2026)
This study investigates the use of phrasal verbs in undergraduate academic writing, focusing on their syntactic features and semantic transparency in relation to academic formality. Despite prescriptive norms favoring explicit and Latinate vocabulary, students frequently employ phrasal verbs, which can introduce ambiguity or informal tones. The study aims to identify the types of phrasal verbs in undergraduate theses, analyze their syntactic characteristics, and interpret how semantic transparency positions them along the formality continuum. A qualitative, corpus-informed approach was adopted, examining 248,987 tokens from undergraduate theses in an English Language Study Program. Phrasal verbs were identified using AntConc and manually verified according to Biber et al.'s (1999) constructional categories. Syntactic features, including transitivity, separability, and particle behavior, were analyzed as indicators of semantic transparency. Exemplification was employed to illustrate patterns and interpret their alignment with academic register expectations. Findings reveal that verb + adverbial particle constructions were the most prevalent, with a preference for inseparability. High semantic transparency phrasal verbs, such as carry out and point out, aligned closely with formal academic norms, while low-transparency verbs, including break down and open up, introduced metaphorical or idiomatic meanings, creating register tension. The study concludes that academic formality is a continuum, and the acceptability of phrasal verbs depends on semantic clarity. These insights inform pedagogical strategies for EAP instruction and suggest further research on cross-disciplinary and longitudinal usage patterns.